Dengue infections during pregnancy: case series from a tertiary care hospital in Sri Lanka - Sampath Kariyawasam; Hemantha Senanayake (Journal of Infection in Developing Countries)
Introduction: Dengue is the most important mosquito-borne disease in Sri Lanka, leading to more than 340 deaths during the last outbreak (≈35,000 reported cases) starting in mid April 2009. The predominant dengue virus serotypes during the last few years have been DENV-2 and DENV-3. Dengue infection in pregnancy carries the risk of hemorrhage for both the mother and the newborn. Other risks include premature birth, fetal death, and vertical transmission.